Excipients choice justification for the creation of Adamantane-1ammonium 2-((5-(adamantane-1-yl)-4-phenyl-4H-1,2,4-triazole-3-yl)thio)acetate tablets by the method of wet granulation (part 2) - V. M. Odyntsova; O. S. Bidnenko (Zaporozhye State Medical University, 2017)
Introduction. The compound adamantane-1-ammonium 2-((5-(adamantane-1-yl)-4-phenyl-4H-1,2,4-triazole-3-yl)thio)acetate was first synthesized at the Department of Toxicology and Inorganic Chemistry (Zaporizhya State Medical University), and received the name "Adatryn". According to pharmacological studies, it shows neuroleptic properties and can be used in pill form, as most neuroleptics. Thus it is important to develop pills technology of adamantane-1-ammonium 2-((5-(adamantane-1-yl)-4-phenyl-4H-1,2,4-triazole-3-yl)thio)acetate. During pharmacological studies the optimum dose at one time was 70 mg. The aim of this work was to study the effect of different groups of excipients on pharmaco-technological properties of adamantane-1-ammonium 2-((5-(adamantane-1-yl)-4-phenyl-4H-1,2,4-triazole-3-yl) thio) acetate tablets. Materials and methods. In the process, we studied four groups of adjuvants, which have various physical and technological properties. In the study of four qualitative factors we used one of dispersion analysis plans - four-factor experiment based on hyper-Greco-Latin square. 16 Excipients were studied, most of which have appeared on the market in recent years and there is no information about their use in pharmaceutical technology in creation of tablet dosage forms. In the experiments we used modern equipment to determine the mass uniformity of drugs, abrasion (abrasion device to determine Pharmatest D-63512 Hainburg, Germany), the time of disintegration (ERWEKA D-63150, Germany), and drugpres (Belorussia). Results and discussion. Given pharmaco-technological properties and the results of morphometric studies proposed a method of wet granulation to obtain adamantan-1-ammonium 2-((5-(adamantan-1-yl)-4-phenyl-4H-1,2,4-triazole-3-yl)thio)acetate tablets. Conclusions. The influence of four groups of auxiliary substances on the technological characteristics of the adamantan-1-ammonium 2-((5-(adamantan-1-yl)-4-phenyl-4H-1,2,4-triazole-3-yl)thio)acetadote tablets, has confirmed the possibility of their obtaining by method of direct pressing. Optimal excipients and the composition of the drugs have been chosen.